2021
DOI: 10.1088/1748-605x/abc7f1
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel-mediated local delivery of dexamethasone reduces neuroinflammation after traumatic brain injury

Abstract: Excessive and prolonged neuroinflammation leads to neuronal cell death and limits functional recovery after traumatic brain injury (TBI). Dexamethasone (DX) is a steroidal anti-inflammatory agent that is known to attenuate early expression of pro-inflammatory cytokines associated with activated microglia/macrophages. In this study, we investigated the effect of dexamethasone-conjugated hyaluronic acid (HA-DXM) incorporated in a hydrolytically degradable, photo-cross-linkable poly (ethylene) glycol-bis-(acryloy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 41 publications
(56 reference statements)
4
18
0
Order By: Relevance
“…Interestingly, relatively low dose DEX administration (1 mg/kg, intraperitoneal injection) has been shown to attenuate inflammation and decrease ED1-positive cells and three markers of inflammatory activation of microglia/macrophage in murine models of traumatic brain injury (TBI) [ 12 , 45 ]. Similar results were found with hydrogel-mediated local delivery of dexamethasone that reduced neuroinflammation and improved functional motor recovery [ 46 ]. Another study reported that dexamethasone alone (0.025 mg/kg) and the co-administration of melatonin and dexamethasone 24 h after TBI improved locomotor function and brain injury [ 47 ].…”
Section: Discussionsupporting
confidence: 80%
“…Interestingly, relatively low dose DEX administration (1 mg/kg, intraperitoneal injection) has been shown to attenuate inflammation and decrease ED1-positive cells and three markers of inflammatory activation of microglia/macrophage in murine models of traumatic brain injury (TBI) [ 12 , 45 ]. Similar results were found with hydrogel-mediated local delivery of dexamethasone that reduced neuroinflammation and improved functional motor recovery [ 46 ]. Another study reported that dexamethasone alone (0.025 mg/kg) and the co-administration of melatonin and dexamethasone 24 h after TBI improved locomotor function and brain injury [ 47 ].…”
Section: Discussionsupporting
confidence: 80%
“…Dexamethasone-21-phosphate is a synthetic glucocorticoid steroid with anti-inflammatory activity. DEX can therefore play an important role in TBIs due to its ability to bind to astrocyte glucocorticoid receptors and prevent the proliferation of astrocytes [40,41]. Furthermore, DEX can lower the production of cytokines such as IL-1β, INF-γ and TNF-α [40].…”
Section: In Vitro Degradation Of Proteosaccharide Scafffoldsmentioning
confidence: 99%
“…It has advantages in the treatment of diseases like TBI where damage factors exist for a prolonged period. Jeong et al placed dexamethasone in a hydrogel constructed by PEG-bis-AA/HA [photo-cross-linkable poly (ethylene) glycol-bis-(acryloyloxy acetate)/hyaluronic acid], demonstrating that compared with traditional intraperitoneal injection, this new drug delivery strategy markedly reduced the dosage of dexamethasone, as much as half above ( 48 ).…”
Section: Drug Delivery With Hydrogelsmentioning
confidence: 99%